ICE-DAMMED LAKE OUTBURST FLOODS IN THE ALTAI MOUNTAINS, SIBERIA A REVIEW WITH LINKS FOR FURTHER READINGS - Herget, Jurgen (Федеральное государственное бюджетное образовательное учреждение высшего профессионального образования "Национальный исследовательский Томский государственный университет", 2012)
This review focuses on selected attempts to reconstruct the ice-dammed lake outburst flood in the valley-bottom of the Chuja River, the main tributary of the Katun River, which is the major source of discharge to the Ob River, while several previous publications present general reviews based on the state of knowledge available at the time of publication. Other studies focus on special aspects, for example, Parnachov and Carling et al. on the geology of giant bars, Carling on the gravel dunes, Reuter et al., on the age of the outburst floods, or Borodavko and Carling et al. on the ice-dammed lake itself. Recent investigations will provide more detailed information regarding the age of the floods. In the review papers mentioned above, the majority of dated flood-related features indicate ages between 40 and ~17 ka. Some of the dates are based on luminescence methods, for which methodological problems make older applications doubtful (Carling, personal comm.). The different attempts to estimate flow conditions of the Pleistocene outburst floods in Altai Mountains result in data for flow velocity and discharge of the flood's peak and unspecified stages of the waning flood. Based on the conservative estimate of the peak discharge to be about 10000000 m.s-1 and assuming that the entire lake basin, with a volume of 607 km., drained during the outburst a hydrograph can be generated. The hydrograph indicates a flood that did not last for more than 2-3 days. The duration of the flood was determined by the integral curve based on the limitations of the drained volume (= integral) and the peak discharge. Advanced modelling of unsteady two-dimensional flow confirms this magnitude. From a negligible baseflow, an abrupt rise of the hydrograph represents the outburst flood wave, which reached peak discharge values almost immediately. It should be noted that the hypothetical hydrograph does not consider ponding effects along the flood's pathway. Consequently, a tendency towards underestimation of the duration of the flood is inherent. Compared with the earlier estimates of the peak discharge of the outburst flood the new calculations give a slightly higher discharge magnitude. Considering the fact that the present study is based on larger number of palaeostage indicators and also includes the calculation of the discharge downstream of the former ice-dam, the new estimations appear reliable and contain several elements of conservative assessment.